His secret mistress - Maxwell, Cathy (Maxwell, Cathy. Logical man's guide to dangerous women novel., 2020)
Brandon Balfour made the mistake of trusting his heart to the exquisite, strong-willed actress Kate Addison, with whom he shared one intimate night before fate intervened. Now a decade later, Brandon is a leading member of the Logical Men's society--for no woman since Kate has managed to captivate him. To Kate, the memory of that night still burns strongly, because it was followed by a stunning betrayal. A chance encounter may have brought Brandon back into her life, but that doesn't mean Kate will ever forgive him. She's vowed to make him pay--even as she realizes the promises of the young love they once shared are still etched upon her heart... Loving her exiled him. Trusting him ruined her. And now, a clash of passions threatens everything each of them ever desired.